Fluid Ferroelectric Filaments - Marcell T. Máthé; Kelum Perera; Ágnes Buka; Péter Salamon; Antal Jákli (Advanced Science, 2024)
Abstract Freestanding slender fluid filaments of room‐temperature ferroelectric nematic liquid crystals are described. They are stabilized either by internal electric fields of bound charges formed due to polarization splay or by external voltage applied between suspending wires. The phenomenon is similar to those observed in dielectric fluids, such as deionized water, except that in ferroelectric nematic materials the voltages required are three orders of magnitudes smaller and the aspect ratio is much higher. The observed ferroelectric fluid threads are not only unique and novel but also offer measurements of basic physical quantities, such as the ferroelectric polarization and viscosity. Ferroelectric nematic fluid threads may have practical applications in nano‐fluidic micron‐size logic devices, switches, and relays.